Sub-Saharan African agricultural research: Recent investment trends - Beintema, Nienke M.; Stads, Gert-Jan (SAGE Publications, 2004)
Following two decades of increasing investments, growth in public agricultural research spending in Sub-Saharan Africa stagnated during the 1980s and 1990s at an average rate of about 1% per year. Nonetheless, this continent-wide trend masks significant variation among countries. During 1991–2000, about half the countries in the authors’ 27-country sample experienced negative annual growth in total agricultural research and development (R&D) spending. Declines often resulted from political unrest or the completion of large donor-funded projects. The majority of African agricultural research is still conducted by the government sector, with the private for-profit sector accounting for only a small, but seemingly increasing, share of total research expenditures.